2009
DOI: 10.4064/ba57-1-8
|View full text |Cite
|
Sign up to set email alerts
|

On Weak Tail Domination of Random Vectors

Abstract: Motivated by a question of Krzysztof Oleszkiewicz we study a notion of weak tail domination of random vectors. We show that if the dominating random variable is sufficiently regular weak tail domination implies strong tail domination. In particular positive answer to Oleszkiewicz question would follow from the so-called Bernoulli conjecture.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…We will use the following comparison theorem from [20] (see also Theorem 2.5 in [10]), which is based on earlier work in [5]. It will allow us to reduce the general case of matrices with i.i.d.…”
Section: Generalization To Different Distributionsmentioning
confidence: 99%
“…We will use the following comparison theorem from [20] (see also Theorem 2.5 in [10]), which is based on earlier work in [5]. It will allow us to reduce the general case of matrices with i.i.d.…”
Section: Generalization To Different Distributionsmentioning
confidence: 99%
“…The first shows that if a Bernoulli vector Y weakly dominates random vector X then Y strongly dominates X (cf. [8]).…”
Section: Selected Applicationsmentioning
confidence: 99%
“…By the Bobkov-Nazarov Theorem [7] they are (κ, L)-weakly dominated by the vector Y = (y 1 , ..., y n ), and κ and L are absolute constants. In [18], Lata la showed that as in (1.6), for every…”
Section: Introductionmentioning
confidence: 99%